Two new species of the genus Hercostomus from Taiwan, China (Diptera, Dolichopodidae) - Zhang, Lili; Yang, Ding; Masunaga, Kazuhiro (Zootaxa, 2005)
The following two species of the genus Hercostomus from Taiwan are described as new to science: Hercostomus (Hercostomus) siveci sp. nov. and H. (H.) taipeiensis sp. nov. Their relationships with related species are discussed.